Properties of Oat and Barley Hulls and Suitability for Food Packaging Materials - Kärkönen, Anna; Korpinen, Risto; Järvenpää, Eila; Aalto, Angela; Saranpää, Pekka (Informa UK Limited, 2022)
The fiber length, chemical composition, and mycototoxins of oat and barley hulls were analyzed in order to study the suitability to utilize hulls for paper and paperboard manufacturing. Oat fibers were observed to be slightly longer than those of barley (0.80 ± 0.19 mm and 0.51 ± 0.17 mm, respectively). There were no differences in the composition of the hemicellulose sugars, with the predominance of xylose and glucose. The amount of Klason lignin in oat and barley hulls was at almost the same level (23% and 25% of dry weight, respectively). Guaiacyl (G) units derived from coniferyl alcohol dominated as shown by pyrolysis-GC-MS. To achieve fibrillation beneficial for the papermaking, oat and barley hulls were refined with a disc refiner. Oat hulls were observed to be harder than barley hulls. This affected both calendering and the appearance of the sheets produced. Laboratory sheets were prepared in a sheet-former with different percentage of softwood pulp and oat and barley hulls. Hull-containing paper mostly met the same quality requirements as the commercial paper except for the burst strength in sheets containing either species’ hulls, and the tensile strength in sheets containing barley hulls.
Keywords: kaura; ohra; kuori; paperinvalmistus; kiertotalous; kuidut